Preparation method and application of MOF-on-MOF material

By using the preparation method of MOF-ON-MOF materials in the electro-catalytic oxygen reaction, the combination reaction of NI-MOF and FE2CO (μ3-O) clusters is used to solve the poor electrical catalytic performance and stability of the existing MOF materials. High problems have achieved efficient and stable electrical catalytic effects in the field of electrolytic hydrogen.

CN119350642APending Publication Date: 2025-01-24CHANGSHU INSTITUTE OF TECHNOLOGY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411476946.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing MOF materials have poor electrocatalytic performance and low stability in electrocatalytic oxygen evolution reactions, making it difficult to meet the needs of electrolytic water hydrogen production technology.

Method used

The preparation method of MOF-ON-MOF materials is used to prepare NI-MOF and FE2CO (μ3-O) clusters first, and then reacts with a specific ratio under normal temperature conditions to synthesize the MOF-ON-MOF material. This method is simple and low in cost, which can improve the electrocatalytic activity and stability of the material.

Benefits of technology

The prepared MOF-ON-MOF material shows excellent electrocatalyst activity and stability in the electro-catalytic oxygen response, which is especially suitable for electrolytic hydrogen-making fields, solving the scarcity and high cost of traditional catalyst materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350642A_ABST
    Figure CN119350642A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an MOF-on-MOF material, and belongs to the technical field of electrocatalysts.The preparation method comprises the steps that firstly, nickel acetate tetrahydrate and terephthalic acid are added into a mixed solvent composed of deionized water and N, N-dimethylacetamide, stirring reaction is conducted at the temperature of 140-160 DEG C, and Ni-MOF is synthesized; mixing and dissolving ferric nitrate nonahydrate and cobalt nitrate in a molar ratio of 1: 5 in deionized water, then adding a sodium acetate aqueous solution, and synthesizing a Fe2Co (mu3-O) cluster after stirring reaction; and then adding the Ni-MOF and the Fe2Co (mu3-O) cluster into deionized water, carrying out ultrasonic treatment, carrying out solid-liquid separation, and washing and drying a solid product to obtain the Ni-MOF / Fe2Co (mu3-O) cluster. Compared with an existing method, the method is easy to operate and low in cost, and the prepared MOF-on-MOF material has excellent electrocatalytic activity and stability in an electrocatalytic oxygen evolution reaction and is particularly suitable for being used in the field of hydrogen production through water electrolysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of a MOF-on-MOF material and application thereof, and belongs to the technical field of electrocatalysts. Background Art

[0002] As the global energy crisis and environmental problems become increasingly serious, the development of efficient, clean and sustainable energy conversion and storage technologies has become a current research hotspot. Hydrogen production by water electrolysis is a clean energy technology with broad application prospects. As one of the half-reactions in the process of hydrogen production by water electrolysis, the catalytic performance of OER directly determines the overall efficiency of hydrogen production by water electrolysis. Therefore, the development of efficient and stable OER electrocatalysts is of great significance to promote the development of water electrolysis hydrogen production technology. Traditional precious metal-based catalyst materials show high activity in OER, but their scarcity and high cost limit their large-scale application. Therefore, finding alternative non-precious metal catalysts has become a research hotspot.

[0003] Metal-organic frameworks (MOFs) are a class of crystalline materials with high specific surface area, adjustable pore structure and diversified chemical functions, and are considered to be potential alternative catalysts. The metal nodes in MOFs can serve as catalytic active centers and can provide a rich chemical environment to regulate electron transport and the surface properties of the catalyst. Many literature reports show good electrocatalytic performance such as low overpotential and small Tafel slope. This is mainly due to the rich electrocatalytic active sites of MOF materials, which are derived from their inherent porosity and hybrid properties. The crystalline properties of metal-organic frameworks enable us to design and adjust them at the molecular level to enhance catalytic activity, but current MOF materials still generally have problems with poor electrocatalytic performance and poor stability.

[0004] MOF-on-MOF is a nanocomposite material composed of homogeneous or heterogeneous structures assembled from MOF units with different structures and morphologies, which exhibits significant advantages in many aspects. The first is tunability and hierarchical nanostructure. Compared with single MOF, dual MOF-on-MOF composite materials have unprecedented tunability, and their structure and performance can be customized and optimized according to application requirements. In addition, the nanostructure of this composite material presents hierarchical characteristics, which makes it possible to achieve more complex and sophisticated functions. The second is synergistic effect and performance enhancement: the heterogeneous structure of MOF-on-MOF enables synergistic effects between different MOF components, thereby significantly enhancing the overall performance of the composite material. This synergistic effect enables MOF-on-MOF to have higher efficiency and better performance in the fields of gas storage and separation, catalysis, luminescence and sensing. In addition, it also has multifunctionality and modular design: by introducing MOFs with different functions into a modular MOF matrix, a multi-functional hybrid system with multiple functions can be constructed. This versatility enables MOF-on-MOF to meet the needs of complex application scenarios and provides strong support for the development of new multifunctional materials. Finally, there is diversity in the growth methods: due to the differences in inorganic metals and organic ligands, the lattice parameters in the a, b, and c directions in the single unit cell can cause subtle or large structural differences. This leads to composite materials with different growth methods to obtain secondary MOFs grown from the initial MOF, thus providing more preparation options and flexibility. The assembly of different metal-organic frameworks (MOFs) building blocks into hybrid MOF-on-MOF heterostructures has broad prospects in the fields of chemistry and materials science, but the development of ternary MOF-on-MOF heterostructures with controllable structural and compositional complexity is challenging, and MOF-on-MOF as electrocatalysts still faces some challenges in practical applications, such as stability, reproducibility, and large-scale production. Summary of the invention

[0005] The purpose of the present invention is to solve the deficiencies of the prior art and provide a method for preparing a MOF-on-MOF material. The method is simple to operate and low in cost. The prepared MOF-on-MOF material has excellent electrocatalytic activity and stability in the electrocatalytic oxygen evolution reaction.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing a MOF-on-MOF material comprises the following steps:

[0008] (1) Preparation of Ni-MOF

[0009] Add nickel acetate tetrahydrate and terephthalic acid to a mixed solvent consisting of deionized water and N,N-dimethylacetamide, stir and mix evenly, then stir and react at 140-160°C for 10-15h, cool to room temperature after reaction, separate the solid and liquid, wash, and vacuum dry to obtain Ni-MOF;

[0010] (2) Preparation of Fe2Co(μ3-O) clusters

[0011] The ferric nitrate nonahydrate and cobalt nitrate in a molar ratio of 1:5 were mixed and dissolved in deionized water to obtain a mixed solution of ferric nitrate and nickel nitrate, and a sodium acetate aqueous solution was added. After stirring for reaction, the mixture was filtered, washed, and vacuum dried to obtain Fe2Co(μ3-O) clusters.

[0012] (3) Preparation of MOF-on-MOF materials

[0013] Ni-MOF and Fe2Co(μ3-O) clusters were added to deionized water and ultrasonically treated for 2 to 4 hours, followed by solid-liquid separation. The solid product was washed and dried to obtain MOF-on-MOF material.

[0014] Furthermore, in step (1), the molar ratio of nickel acetate tetrahydrate to terephthalic acid is 1:1.

[0015] Furthermore, in step (1), the volume ratio of water to p-methylacetamide in the mixed solvent is 1:1.

[0016] Furthermore, in steps (1) and (2), the vacuum drying temperature is 60°C.

[0017] Furthermore, in step (2), the molar ratio of sodium acetate to ferric nitrate nonahydrate is (14-16):1.

[0018] Furthermore, in step (3), the mass ratio of the Ni-MOF to the Fe2Co(μ3-O) cluster is 1:(0.5-2).

[0019] The MOF-on-MOF material was prepared by the above method.

[0020] The MOF-on-MOF material prepared by the above method is used as an electrocatalyst in hydrogen production by water electrolysis.

[0021] Beneficial effects of the invention: The invention provides a method for preparing a MOF-on-MOF material, wherein Ni-MOF and Fe2Co(μ3-O) are first synthesized separately, and then Ni-MOF is used as a precursor to react with Fe2Co(μ3-O) in a specific ratio to obtain a MOF-on-MOF material under room temperature conditions. The method is simple to operate and low in cost. The prepared MOF-on-MOF material has excellent electrocatalytic activity and stability in an electrocatalytic oxygen evolution reaction, and is particularly suitable for use in the field of hydrogen production by electrolysis of water. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 XRD patterns of MOF-on-MOF materials prepared in Examples 1-3;

[0023] Figure 2 The infrared spectra of the MOF-on-MOF materials prepared in Examples 1-3;

[0024] Figure 3 TEM image of the MOF-on-MOF material prepared in Example 1;

[0025] Figure 4 TEM image of the MOF-on-MOF material prepared in Example 2;

[0026] Figure 5 Element distribution diagram of the MOF-on-MOF material prepared in Example 2;

[0027] Figure 6 Elemental analysis diagram of the MOF-on-MOF material prepared in Example 2;

[0028] Figure 7 This is the XPS spectrum of the MOF-on-MOF material prepared in Example 2;

[0029] Figure 8 LSV curves and Tafel slope diagrams of electrodes prepared using the MOF-on-MOF materials of Examples 1-3;

[0030] Fig. 9 ECSA curves of electrodes prepared using the MOF-on-MOF materials of Examples 1-3;

[0031] Fig.10 The electrochemical impedance spectra of the electrodes prepared using the MOF-on-MOF materials of Examples 1-3. DETAILED DESCRIPTION

[0032] The technical solution of the present invention is clearly and completely described below in conjunction with the accompanying drawings and specific embodiments.

[0033] Example 1

[0034] A method for preparing a MOF-on-MOF material comprises the following steps:

[0035] (1) Preparation of Ni-MOF

[0036] 2mmol nickel acetate tetrahydrate and 2mmol terephthalic acid were added to a mixed solvent consisting of 24mL deionized water and 24mL N,N-dimethylacetamide, stirred and mixed evenly, and then stirred and reacted at 150°C and 800r / min for 12h. After the reaction, it was naturally cooled to room temperature, and then centrifuged at 8000r / min. The obtained solid product was washed twice with deionized water and anhydrous ethanol, and finally dried in vacuum at 60°C to obtain Ni-MOF;

[0037] (2) Preparation of Fe2Co(μ3-O) clusters

[0038] Ferric nitrate nonahydrate (8 g, 0.02 mol) and cobalt nitrate (29 g, 0.1 mol) were mixed and dissolved in 70 mL of deionized water to obtain a mixed solution of ferric nitrate and cobalt nitrate; sodium acetate trihydrate (42 g, 0.31 mol) was dissolved in 70 mL of deionized water to obtain a sodium acetate aqueous solution; sodium acetate aqueous solution was added to the mixed solution of ferric nitrate and cobalt nitrate, stirred for reaction, filtered, and the solid product was washed twice with deionized water and ethanol respectively, and finally vacuum dried at 60° C. to obtain Fe2Co(μ3-O) clusters;

[0039] (3) Preparation of MOF-on-MOF materials

[0040] 50 mg Ni-MOF and 25 mg Fe2Co(μ3-O) clusters were added to 20 mL deionized water, ultrasonically treated for 3 h, and then centrifuged at 8000 r / min. The solid product was washed with deionized water and anhydrous ethanol respectively, and finally dried to obtain MOF-on-MOF material, recorded as Fe2Co@Ni-MOF-1.

[0041] Example 2

[0042] In step (3), the amount of Fe2Co(μ3-O) cluster used is 50 mg, and the rest is the same as in Example 1. The obtained MOF-on-MOF material is recorded as Fe2Co@Ni-MOF-2.

[0043] Example 3

[0044] In step (3), the amount of Fe2Co(μ3-O) cluster used is 100 mg, and the rest is the same as in Example 1. The obtained MOF-on-MOF material is recorded as Fe2Co@Ni-MOF-3.

[0045] Figure 1 From the XRD diagram of the MOF-on-MOF material prepared in Example 1-3, it can be seen that for Ni-MOF, it is consistent with the fitting value of the fitted Ni-BDC, indicating that we have successfully synthesized a Ni-based MOFs material with a two-dimensional structure. The rich coordinated unsaturated sites on its surface provide the possibility for competitive coordination of Fe2Co(μ3-O). When Ni-MOF reacts with Fe2Co(μ3-O) clusters, the obtained MOF-on-MOF type material still maintains the main skeleton structure, but with the increase of Fe2Co(μ3-O) feed amount, the characteristic diffraction peak represented by 2θ=9.24° gradually weakens, and a new set of diffraction peaks appears, corresponding to the currently reported MIL-53(Fe). The Fe2Co@Ni-MOF-3 phenomenon obtained by reacting 100g Fe2Co(μ3-O) is most obvious, indicating that a new MOFs material with the same configuration as the MIL-53 material is indeed generated on the surface of Ni-MOF, proving that the synthesis of MOF-on-MOF material can be achieved through our synthesis method.

[0046] Figure 2 The infrared spectrum of the MOF-on-MOF material prepared in Example 1-3 shows that the absorption spectrum of Ni-MOF is about 3500 cm -1 There is a broad and strong absorption peak at about 1600 cm -1 and about 800cm -1 The absorption spectrum of Fe2Co@Ni-MOF-3 is similar to that of Ni-MOF, but at about 1600 cm -1 The absorption peak at about 800 cm -1 The absorption peak at about 3500cm is relatively weak. This may mean that there is more iron in the Fe2Co@Ni-MOF-3 material or that it interacts with other elements. The absorption spectrum of Fe2Co@Ni-MOF-2 is different from that of the first two materials. -1 The absorption peak at about 1600 cm -1 and about 800cm -1 The absorption peak at 1600 cm is also relatively strong. This may suggest that the Fe2Co@Ni-MOF-2 material has higher crystallinity and stronger chemical bonding. The absorption spectrum of Fe2Co@Ni-MOF-1 shows more fluctuations and complexity, especially at about 1600 cm -1 and about 800cm -1 The absorption peak at is the most significant, which may reflect that the properties and structure of Fe2Co@Ni-MOF-1 materials are more diverse and complex.

[0047] Figure 3 This is a TEM image of the MOF-on-MOF material prepared in Example 1, wherein: Figure 3 a and Figure 3 b is the TEM image of Ni-MOF at different scales. Figure 3 c and Figure 3 d is the TEM image of MOF-on-MOF materials at different scales. As shown in the figure, Ni-MOF presents a relatively uniform flaky morphology, in which a small number of nanosheets are stacked, and most of them are dispersed. Their sizes are between 300 and 400 nm, the thickness is relatively thin, and the surface is smooth without obvious nanoparticles. The surface of Fe2Co@Ni-MOF-1 begins to become rough, and a large number of nanosheets aggregate to form a flaky aggregate morphology of about 2 to 3 μm.

[0048] Figure 4 This is the TEM image of the MOF-on-MOF material prepared in Example 2. Figure 4 a and Figure 4 b are TEM images of MOF-on-MOF materials at different scales. It can be seen that when the Fe2Co(μ3-O) clusters are further increased, Ni-MOFs and Fe2Co(μ3-O) clusters react at a mass ratio of 1:1 to obtain Fe2Co@Ni-MOF-2. The changes in the MOFs surface can be observed more intuitively. The surface is no longer smooth and has more nanoparticles distributed. Figure 1 Based on XRD tests, we infer that these nanoparticles are new MOFs materials with the same structure as MIL-53.

[0049] Figure 5 This is the element distribution diagram of the MOF-on-MOF material prepared in Example 2. As shown in the figure, Fe2Co@Ni-MOF-2 is mainly composed of five elements: Ni, Fe, Co, C, and O, and the five elements are evenly distributed, proving that the newly introduced Fe and Co elements not only exist on the surface of Ni-MOFs in the form of new MOFs, but are also evenly distributed.

[0050] Figure 6 This is the elemental analysis diagram of the MOF-on-MOF material prepared in Example 2. As shown in the figure, all five elements are present in Fe2Co@Ni-MOF-2, with the Fe:Co ratio being 1.93:1, which is consistent with the ratio in the raw material Fe2Co(μ3-O) cluster, further proving that we have successfully synthesized MOF-on-MOF type MOFs material.

[0051] Figure 7This is the XPS spectrum of the MOF-on-MOF material prepared in Example 2, wherein: Figure 7 (a) is the full spectrum, Figure 7 (b) is the C1s diagram, Figure 7 (c) is the O1s diagram, Figure 7 (d) Ni 2p 3 / 2 picture, Figure 7 (e) is Fe 2p 3 / 2 picture, Figure 7 (f) is Co 2p 3 / 2 As shown in the figure, all elements in Fe2Co@Ni-MOF-2, such as Ni, C, O, Fe, Co, etc., can be observed in the full XPS spectrum. The entire binding energy is through the C1s main peak (sp at 284.8 eV). 2 C—C bonds) were calibrated, and the high-resolution spectra of Ni 2p were attributed to Ni 2+ and Ni 3+ . 3+ The content of high valence state in Ni-MOFs increased significantly, which may be due to the regulation of FeCo-MIL-53 on the surface. In addition, it can be seen from the figure that there is an obvious peak at around 860eV, which is the 2p 3 / 2 In addition, there are several other smaller peaks corresponding to the 2p 1 / 2 orbital and other possible satellite peaks. The position and intensity of these peaks provide information about the environment around the nickel atom. We can see that the 2p 3 / 2 The binding energy of the orbital is about 860 eV, and the 2p 1 / 2 The binding energy of the orbital is slightly lower. This difference is usually caused by the energy difference between the orbitals and is also related to the oxidation state of the nickel atom. The O 1s peak is located at about 530 eV, indicating that the sample contains oxygen, and its binding energy is about 530 eV. The peak is relatively sharp, indicating that the chemical environment of the oxygen element is relatively simple. In addition, the 2p high-resolution diffraction peaks of Fe and Co are mainly attributed to Co due to their low content and the influence of background noise. 2+ and Fe 3+ The valence state of MOF-on-MOF is consistent with the previous characterization results, confirming the successful synthesis of MOF-on-MOF.

[0052] The MOF-on-MOF material prepared in Example 1-3 was prepared into an electrode, and then the electrocatalytic performance was tested. Preparation method of the electrode: prepare a working electrode, clean the working electrode with alcohol and ultrapure water, and gently wipe the electrode surface with a clean paper towel. Then prepare a dispersion, disperse 5mg MOF-on-MOF material and 5mg conductive carbon black in a mixture of 750μL anhydrous ethanol, 200μL isopropanol and 50μL Nafion solution, and then ultrasonicate for 1 hour to prepare an electrocatalytic ink slurry, after which 10μL of the ink slurry is dropped onto a polished GC disk electrode and dried naturally at room temperature. The working electrode is then connected to an electrochemical workstation, and the parameters are set to test the electrochemical performance using linear voltammetry.

[0053] Figure 8 The LSV curve and Tafel slope diagram of the electrode prepared using the MOF-on-MOF material of Examples 1-3, wherein Figure 8 (a) is the LSV curve, Figure 8 (b) is the Tafel slope diagram, Figure 8 (c) is the overpotential test result. It can be seen that the performance of MOF-on-MOF materials with gradually increasing Fe2Co(μ3-O) content has been further improved, and its overpotential has gradually decreased from 493.5mV to 448.2mV and 415mV. More obviously, the overpotential in the high voltage area decreases more significantly, which further illustrates that Fe2Co(μ3-O) can further improve its electrocatalytic oxygen evolution performance by regulating the morphology and structure of MOF-on-MOF materials. The Tafel diagram intuitively shows the electrochemical kinetic behavior of various materials in the electrocatalytic process. Compared with MOF-on-MOF materials with low Fe2Co(μ3-O) content, the Tafel slope has increased from the original 160.1mV·dec -1 They dropped to 140.3mV·dec -1 and 104.9mV·dec -1 , which further illustrates that Fe2Co(μ3-O) can not only reduce the overpotential of MOF-on-MOF materials, but also accelerate the kinetic behavior of the electrocatalytic oxygen evolution process.

[0054] Fig. 9 is the ECSA curve of the electrode prepared using the MOF-on-MOF material of Examples 1-3, wherein, Fig. 9 (a) is the ECSA curve of the electrode prepared by Fe2Co@Ni-MOF-1. Fig. 9 (b) is the ECSA curve of the electrode prepared by Fe2Co@Ni-MOF-2. Fig. 9 (c) is the ECSA curve of the electrode prepared by Fe2Co@Ni-MOF-3. Fig. 9 (d) is the quantitative evaluation result of ECSA. It can be seen from the figure that the double layer capacitance of Fe2Co@Ni-MOF-1, Fe2Co@Ni-MOF-2, and Fe2Co@Ni-MOF-3 are close. The experimental results show that the electrochemical active area of ​​MOF-on-MOF materials does not change significantly with the change of Fe2Co(μ3-O) content, which further proves that the content of Fe2Co(μ3-O) does not change the active area of ​​MOFs materials, but improves the electrocatalytic OER performance by changing the local electronic structure of the active sites and increasing the intrinsic activity of the active sites.

[0055] Fig.10 The electrochemical impedance spectra of the electrodes prepared using the MOF-on-MOF materials of Examples 1-3 show that Fe2Co@Ni-MOF-3 has a smaller semicircle radius than the other two samples, indicating that its resistance during the electrochemical reaction is smaller, showing that it has lower charge transfer resistance and faster electrocatalytic kinetics, which is consistent with the conclusions obtained from the previous polarization curves and Tafel diagrams.

Claims

1. A method for preparing a MOF-on-MOF material, characterized in that: The steps include: (1) Preparation of Ni-MOF Add nickel acetate tetrahydrate and terephthalic acid to a mixed solvent consisting of deionized water and N,N-dimethylacetamide, stir and mix evenly, then stir and react at 140-160°C for 10-15h, cool to room temperature after reaction, separate the solid and liquid, wash, and vacuum dry to obtain Ni-MOF; (2) Preparation of Fe2Co(μ3-O) clusters The ferric nitrate nonahydrate and cobalt nitrate in a molar ratio of 1:5 were mixed and dissolved in deionized water to obtain a mixed solution of ferric nitrate and nickel nitrate, and a sodium acetate aqueous solution was added. After stirring for reaction, the mixture was filtered, washed, and vacuum dried to obtain Fe2Co(μ3-O) clusters. (3) Preparation of MOF-on-MOF materials Ni-MOF and Fe2Co(μ3-O) clusters were added to deionized water and ultrasonically treated for 2 to 4 hours, followed by solid-liquid separation. The solid product was washed and dried to obtain MOF-on-MOF material.

2. The method for preparing the MOF-on-MOF material according to claim 1, characterized in that: In step (1), the molar ratio of nickel acetate tetrahydrate to terephthalic acid is 1:

1.

3. The method for preparing the MOF-on-MOF material according to claim 1, characterized in that: In step (1), in the mixed solvent, the volume ratio of water to p-methylacetamide is 1:

1.

4. The method for preparing the MOF-on-MOF material according to claim 1, characterized in that: In steps (1) and (2), the vacuum drying temperature is 60°C.

5. The method for preparing the MOF-on-MOF material according to claim 1, characterized in that: In step (2), the molar ratio of sodium acetate to ferric nitrate nonahydrate is (14-16):

1.

6. The method for preparing a MOF-on-MOF material according to any one of claims 1 to 5, characterized in that: In step (3), the mass ratio of the Ni-MOF to the Fe2Co(μ3-O) cluster is 1:(0.5-2).

7. A MOF-on-MOF material prepared by the method according to any one of claims 1 to 6.

8. Use of the MOF-on-MOF material prepared by the method according to any one of claims 1 to 6 as an electrocatalyst in hydrogen production by electrolysis of water.

Citation Information

Cited By

  • MOF-on-MOF material, preparation method and electrochemical energy storage application thereof

    CN120453077A

  • Difunctional electro-catalytic water decomposition material as well as preparation and application thereof

    CN120666390A